HUBUNGAN PENDAPATAN ORANG TUA SISWA DENGAN HASIL BELAJAR IPS SD NEGERI DI WAETUNO RAYA KABUPATEN WAKATOBI - Mirna, Wa Ode (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2021)
This research uses a quantitative descriptive approach using the correlation method. The population of this research is 200 students of grade V SD in Waetuno Raya Village, Wakatobi Regency. Sampling was taken by using Probaliti Sampling, namely Simple Random Sampling, obtained 50 students. Data collection techniques, observation, documentation, questionnaires and tests. The results of this study are based on the results of the discussion of data analysis, it can be concluded that the income level of parents in SD in Waetuno Raya Village, Wakatobi Regency is 15% very high income, 33% high income, 35% medium income and 17% low income based on this research. Parents of students at SD Se- Kelurahan Waetuno Raya, Wakatobi Regency, are in the middle or medium category. From the student learning outcomes, 45 students (90%) completed and 5 students (10%) did not complete so that on average the students at the State Elementary School had high learning outcomes. There is a positive influence on Parents' Income Level with Social Studies Learning Outcomes in SD in Waetuno Raya Village, Wakatobi Regency, which is indicated by a determination coefficient of 0.568, which means that 30% of the Parents Income Level variable affects IPS learning outcomes so that 70% of other factors remain not examined in this study. Based on the results of the analysis, the authors provide some suggestions to parents who should always be motivated by always giving advice and monitoring their children in terms of learning and providing direction about education for their children. Parents should also always provide support in the form of learning facilities and it can also be non-material for their children to always excel